Electrolyte combined additive, electrolyte and lithium ion battery
By using electrolyte combination additives composed of cyanide and boron compounds in lithium-ion batteries, the problem of slow kinetics and intensified interface side reactions in lithium-ion batteries is solved, and higher low-temperature performance and better The dense protective film significantly improves the low-temperature performance of the battery.
Patent Information
- Application Number
- CN202411493593.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-18
AI Technical Summary
Lithium-ion batteries have slow kinetics and intensified interface side reactions under low temperature conditions, making it difficult to meet the demands of the power battery and energy storage markets.
The additive is obtained by combining an electrolyte solution additive, including a cyanide compound and a boron compound. Cyanide compounds have high dielectric constant and low viscosity, and can form CN-Co bonds with the surface of NCM metal oxides, inhibit the electrolyte from directly contacting the positive electrode, and improve the stability of the positive electrode interface. The central B atom of boron compounds is in an electron-deficient state, which can combine with anions to form a complex, inhibit the decomposition reaction of anions, and inhibit its hydrolysis by complexing with PF6-, reducing the deposition of LiF, thereby reducing the cell interface impedance. Improve ionic conductivity.
Through the use of electrolyte combination additives, thinner and denser CEI and SEI protective films can be generated on the surfaces of NCM cathode and graphite anode, removing residual lithium compounds on the surface of positive and negative electrodes, improving the ionic conductivity of the interface film, and significantly improving the low-temperature performance of the battery .
Smart Images

Figure BDA0005100698450000011 
Figure BDA0005100698450000021 
Figure BDA0005100698450000022
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to an electrolyte combination additive, an electrolyte and a lithium ion battery. Background Art
[0002] Lithium-ion batteries are constrained by slow kinetics and intensified interface side reactions at low temperatures (<0°C). Therefore, the low-temperature performance of conventional lithium-ion batteries is difficult to meet the growing needs of the power battery and energy storage markets. + The transport and interfacial reaction of lithium-ion batteries largely determine the low-temperature performance of lithium-ion batteries. Low-temperature improvement additives for lithium-ion battery electrolytes have the characteristics of small dosage and quick effect. Adding additives to improve the low-temperature performance of lithium-ion battery organic electrolytes and thus improve the low-temperature performance of lithium-ion batteries is a current research hotspot and an important development direction in this field in the future. Therefore, finding and developing low-temperature improvement additives has become an important link in the breakthrough of low-temperature performance of lithium-ion batteries. Summary of the invention
[0003] Based on the technical problems existing in the background technology, the present invention proposes an electrolyte combination additive, an electrolyte and a lithium ion battery.
[0004] The present invention provides an electrolyte combination additive, comprising component A and component B, wherein component A is a compound having a structure as shown in formula I, and component B is a compound having a structure as shown in formula II:
[0005]
[0006] In formula I, R1 is a halogen atom or a methoxy group;
[0007] In formula II, R2 is C 1~3 Ester group or C 1~6 Halogenated alkyl.
[0008] The present invention obtains an electrolyte combination additive by compounding a cyanide compound having a structure shown in Formula I and a boron compound having a structure shown in Formula II, wherein the cyanide compound has a high dielectric constant and a low viscosity, and the strongly electronegative cyanide group can form a CN-Co bond with the surface of the NCM metal oxide, inhibiting the electrolyte from directly contacting the positive electrode, thereby improving the stability of the positive electrode interface, and the cyanide group has a strong electrophilic activity, which can react with the water in the electrolyte and the active hydrogen in the positive and negative electrode materials to reduce the decomposition of LiPF6 caused by active hydrogen; the central B atom of the boron compound is in an electron-deficient state, so it has the ability to combine with anions to form a complex and inhibit the decomposition reaction of the anions. And because the boron compound has a higher HOMO energy level, it can be oxidatively decomposed to construct a SEI / CEI membrane protection electrode in priority to the electrolyte. In addition, the boron compound can increase the dissociation degree of LiPF6 and react with PF 6- The complexation of the two inhibits its hydrolysis, reduces the deposition of LiF, thereby reducing the battery interface impedance and improving the ionic conductivity. The present invention uses the two together to play a synergistic role, making it easier to generate thinner and denser CEI and SEI protective films on the surface of the NCM cathode and the graphite anode, while removing residual lithium compounds on the surface of the positive and negative electrodes, improving the ionic conductivity of the interface film, and can greatly improve the low-temperature performance of the battery compared with traditional electrolyte additives.
[0009] Preferably, the component A is one or a combination of compound 1 (CAS: 4640-67-9) and compound 2 (CAS: 3672-47-7):
[0010]
[0011] Preferably, the component B is one or a combination of compound 3 (CAS: 325142-82-3) and compound 4 (CAS: 480425-35-2):
[0012]
[0013] Preferably, the mass ratio of component A to component B is 1:5 to 5:1.
[0014] The present invention also provides a lithium ion battery electrolyte with improved low temperature performance, wherein the components of the electrolyte include a conductive lithium salt, the electrolyte combination additive, other additives and an organic solvent.
[0015] Preferably, the amount of the electrolyte combination additive is 0.1 to 3 wt % of the total mass of the electrolyte.
[0016] Preferably, the other additives are selected from at least one of phenyl sulfone, tris(trimethylsilyl)phosphite, vinyl sulfate, vinyl carbonate, fluoroethylene carbonate, and methylene disulfonate. Preferably, the amount of the other additives is 0.5-3wt% of the total mass of the electrolyte, preferably 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%; the concentration of other additives is limited to the above range, so that the battery can have excellent room temperature cycle performance while having better electrochemical performance.
[0017] Taking into account the selection of a conductive lithium salt that is better compatible with the additive and the battery having better electrochemical performance and room temperature cycle retention rate, preferably, the conductive lithium salt includes a first lithium salt and a second lithium salt, the first lithium salt is lithium hexafluorophosphate, and the second lithium salt is selected from at least one of lithium tetrafluoroborate, lithium dioxalatoborate, lithium difluorooxalatoborate, lithium difluorooxalatophosphate, bis(fluorosulfonyl)imide lithium salt, and bis(trifluoromethylsulfonyl)imide lithium; the molar ratio of the first lithium salt to the second lithium salt is 1:1 to 10:1.
[0018] Preferably, in the electrolyte, the molar concentration of the conductive lithium salt is 0.5-1.5M, for example, 0.5M, 0.75M, 1M, 1.25M, 1.5M; the molar concentration of the conductive lithium salt is limited to the above range, so that the battery can have both better electrochemical performance and room temperature cycle retention rate.
[0019] The organic solvent includes at least one of cyclic carbonates, chain carbonates, and carboxylates; preferably, the cyclic carbonate is selected from at least one of ethylene carbonate, fluoroethylene carbonate, propylene carbonate, butylene carbonate, and γ-butyrolactone; the chain carbonate is selected from at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate; preferably, the carboxylate is selected from at least one of methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, and ethyl butyrate.
[0020] Preferably, the organic solvent is selected from at least one of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and ethyl propionate (EP). The above organic solvents are more compatible with the additives of the present invention, based on which the battery can have better electrochemical performance and capacity retention.
[0021] Preferably, the method for preparing the electrolyte comprises: adding a conductive lithium salt to an organic solvent, and after the conductive lithium salt is completely dissolved, adding the electrolyte combination additive and other additives to obtain an electrolyte; preparing the electrolyte by the above method can make the electrolyte have better performance uniformity.
[0022] The invention also discloses a lithium ion battery, comprising a negative electrode sheet, a positive electrode sheet, a diaphragm arranged between the negative electrode sheet and the positive electrode sheet, and the electrolyte.
[0023] Preferably, the positive electrode sheet comprises a positive electrode material, and the positive electrode material comprises LiNi (1-x-y) Co x Mn y O2, wherein 0≤x≤1, 0≤y≤1; the negative electrode sheet comprises a negative electrode material, and the negative electrode material comprises graphite. The above positive and negative electrode materials are more compatible with the additive of the present invention, so that the lithium-ion battery has a better capacity retention rate and capacity recovery rate.
[0024] Preferably, the charging voltage of the lithium-ion battery is ≤4.8V, preferably 2.8-4.25V.
[0025] The beneficial effects of the present invention are as follows:
[0026] The electrolyte combination additive of the present invention includes a compound with a structure as shown in Formula I and a compound with a structure as shown in Formula II. The combined use of the two compounds has a synergistic effect, making it easier to generate thinner and denser CEI and SEI protective films on the surfaces of NCM cathodes and graphite anodes. At the same time, it has the functions of removing water, reducing acid or complexing, and can remove residual lithium compounds on the surfaces of positive and negative electrodes, improve the ion conductivity of the interface film, and can greatly improve the low-temperature performance of the battery compared with traditional electrolyte additives. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is described in detail below through specific embodiments.
[0028] Example 1
[0029] (1) Preparation of electrolyte: Ethylene carbonate (EC), ethyl propionate (EP) and ethyl methyl carbonate (EMC) were mixed in a mass ratio of EC:EP:EMC=1:1:2, and then 0.7 mol of lithium hexafluorophosphate (LiPF6) and 0.3 mol of lithium bis(fluorosulfonyl)imide (LiFSI) were added. After complete dissolution, 2%wt of compound 1 and 1% of compound 3 were added.
[0030] (2) Preparation of positive electrode: LiNi 0.7 CO 0.1 Mn 0.2 O2, conductive agent SuperP, adhesive PVDF and carbon nanotubes (CNT) were mixed evenly in a mass ratio of 97.5:0.5:1:1 to obtain a positive electrode slurry for lithium-ion batteries, which was coated on aluminum foil for current collectors. The double-sided coating amount was 360 g / m 2, drying at 85°C and then cold pressing; then slitting, slicing, and drying at 85°C for 4 hours under vacuum to obtain a positive electrode sheet for a lithium-ion battery;
[0031] (3) Preparation of negative electrode sheet: Artificial graphite was mixed with conductive agent SuperP, thickener CMC, and adhesive SBR (styrene-butadiene rubber latex) at a mass ratio of 95:1.5:1.0:2.5 to obtain a negative electrode slurry for lithium-ion batteries, which was then coated on both sides of the copper foil with a double-sided coating amount of 230 g / m 2 , drying at 85°C and then cold pressing; then slitting, slicing, and drying at 85°C for 4 hours under vacuum to obtain a negative electrode sheet for a lithium-ion battery;
[0032] (4) Preparation of lithium-ion battery: The positive electrode sheet, negative electrode sheet and separator prepared above were laminated into a battery cell with a thickness of 0.5 mm, a width of 8 mm and a length of 10 mm, and vacuum-baked at 85°C for 48 h. The above-mentioned electrolyte was injected to obtain a lithium-ion battery with a capacity of 3 Ah.
[0033] Examples 2 to 14 and Comparative Examples 1 to 6 change the ratio and type of specific substances in the electrolyte, and refer to the preparation method of Example 1 to obtain lithium ion batteries. The electrolyte formula is shown in Table 1 below.
[0034] The performance of the lithium-ion batteries assembled with the electrolytes of the embodiments and comparative examples was tested, and the test items and test methods were as follows:
[0035] (1) Low temperature DC resistance (DCR)
[0036] After capacity division, the experimental batteries were charged to a charge state of 50% SOC at room temperature. After being left at rest for 10 hours at -25°C, the sampling voltage V0 at the beginning of discharge was recorded. Then, after being discharged at a current of 2C I for 10 seconds, the sampling voltage V1 at the end of discharge was recorded. The initial DC discharge impedance DCR of the experimental battery at low temperature was calculated as (V1-V0) / I. The test results are shown in Table 1.
[0037] (2) Low temperature discharge performance
[0038] After the capacity is divided, the experimental battery is charged and discharged at 0.33C for three weeks at room temperature, and the last cycle of discharge capacity is recorded as C1. Then it is fully charged at 0.33C current I, left to stand at -25℃ for 10h, and then discharged at 0.33C current I until it is empty, and the discharge capacity is recorded as C2. The low temperature capacity retention rate of the experimental battery is calculated as (C2 / C1)*100. The test results are shown in Table 1.
[0039] Table 1 Electrolyte composition and battery performance test results of the embodiments and comparative examples
[0040]
[0041]
[0042] By comparing the initial DCR results of the embodiment and the comparative example at low temperature, it can be seen that compared with the traditional additives (TMSP and MMDS), the electrolyte combination additive of the present invention can effectively reduce the initial DCR of the battery at low temperature.
[0043] By comparing the low-temperature capacity retention rate results of the embodiment with those of the comparative example, it can be seen that compared with the traditional additives (TMSP and MMDS), the electrolyte combination additive of the present invention can effectively improve the low-temperature capacity retention rate.
[0044] From the above, it can be seen that the present invention can significantly improve the low temperature performance of the battery compared with traditional additives by combining the cyanide compound having the structure shown in formula I and the boron compound having the structure shown in formula II. This is because the introduction of the above-mentioned combined additives plays a synergistic role, making the positive and negative electrode films more dense and stable, reducing the positive and negative electrode interface impedance, and at the same time removing the byproducts on the positive and negative electrode surfaces, improving the interface film ion conductivity, thereby greatly improving the low temperature performance of the battery.
[0045] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An electrolyte additive combination, characterized in that: The combined additive comprises component A and component B, wherein component A is a compound having a structure as shown in formula I, and component B is a compound having a structure as shown in formula II: In formula I, R1 is a halogen atom or a methoxy group; In formula II, R2 is C 1~3 Ester group or C 1~6 Halogenated alkyl.
2. The electrolyte additive combination according to claim 1, characterized in that: The component A is one or a combination of compound 1 and compound 2:
3. The electrolyte additive combination according to claim 1, characterized in that: The component B is one or a combination of compound 3 and compound 4:
4. The electrolyte additive combination according to claim 1, characterized in that: The mass ratio of component A to component B is 1:5 to 5:
1.
5. A lithium ion battery electrolyte with improved low temperature performance, characterized in that: The components of the electrolyte include a conductive lithium salt, the electrolyte combination additive according to claim 1, other additives and an organic solvent.
6. The lithium ion battery electrolyte with improved low temperature performance according to claim 5, characterized in that: The amount of the electrolyte combination additive is 0.1-3 wt % of the total mass of the electrolyte.
7. The lithium ion battery electrolyte with improved low temperature performance according to claim 5, characterized in that: The amount of the other additives is 0.5-3wt% of the total mass of the electrolyte; the other additives are selected from at least one of phenyl sulfone, tris(trimethylsilyl)phosphite, vinyl sulfate, vinyl carbonate, fluoroethylene carbonate, and methylene disulfonate.
8. The lithium-ion battery electrolyte with improved low temperature performance according to claim 5, characterized in that: The conductive lithium salt includes a first lithium salt and a second lithium salt, the first lithium salt is lithium hexafluorophosphate, and the second lithium salt is selected from at least one of lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorooxalatophosphate, bis(fluorosulfonyl)imide lithium salt, and bis(trifluoromethylsulfonyl)imide lithium; the molar ratio of the first lithium salt to the second lithium salt is 1:1 to 10:
1.
9. A lithium ion battery, characterized in that: The invention comprises a negative electrode sheet, a positive electrode sheet, a separator arranged between the negative electrode sheet and the positive electrode sheet, and the electrolyte according to any one of claims 5 to 8.
10. The lithium-ion battery according to claim 9, characterized in that: The positive electrode sheet includes a positive electrode material, and the positive electrode material includes LiNi (1-x-y) Co x Mn y O2, wherein 0≤x≤1, 0≤y≤1; the negative electrode sheet comprises a negative electrode material, and the negative electrode material comprises graphite.
Citation Information
Patent Citations
Non-aqueous electrolyte and lithium secondary battery of using same
CN106532120A
Lithium secondary battery electrolyte and lithium secondary battery
CN107403959A
Electrolyte additive, electrolyte and lithium secondary battery
CN113745660A
Electrolyte for improving low-temperature performance and lithium battery
CN118367215A
High-temperature-resistant lithium ion battery electrolyte
CN118486897A